1985
DOI: 10.4012/dmj.4.68
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dentin on Bonding of Composite Resin

Abstract: The effects of preserving conditions and time after extraction of human teeth, as specimens for bond strength of composite resin to the dentin, were investigated by the tensile test method and scanning electron microscopy (SEM).When the teeth were stored in physiologic saline solution, bond strength at 15 minutes after extraction showed the lowest value (13kg/cm2), and at 1 to 12 weeks it was elevated to about 35kg/cm2. However pretreatment with citric acid-FeCl3 solution of dentin surface increased the bond s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In this study we used bovine dentin. Although there may be some differences between bovine cementum and human cementum, it has been reported that the tensile bond strength of resin composite to bovine dentin was similar to that of human dentin under the same conditions 22. Hence we are of the opinion that information about 4‐META/MMA‐TBB resin adhesion to cementum using bovine cementum is valid to make inferences for human study.…”
Section: Discussionmentioning
confidence: 86%
“…In this study we used bovine dentin. Although there may be some differences between bovine cementum and human cementum, it has been reported that the tensile bond strength of resin composite to bovine dentin was similar to that of human dentin under the same conditions 22. Hence we are of the opinion that information about 4‐META/MMA‐TBB resin adhesion to cementum using bovine cementum is valid to make inferences for human study.…”
Section: Discussionmentioning
confidence: 86%